2014
DOI: 10.1371/journal.pone.0108472
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Ileal Mucosa Bacteria Related to Diet Complexity and Growth Performance in Young Pigs

Abstract: BackgroundEvaluation of the prolonged impact of weaning diet on ileal mucosa bacteria and during periods of reduced and improved growth was conducted using 454 pyrosequencing.Methodology/Principal FindingsWeaned pigs were fed HIGH or LOW complexity diets, with or without antibiotics, for 6 weeks, followed by a common grower diet. Pigs were killed at 2 (n = 4 or 5) and 8 (n = 6) weeks post-weaning (periods of reduced and improved growth, respectively). Mucosal bacteria were removed; DNA was extracted and amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…The phyla profile in sow‐fed piglets in this study is similar to that reported in previous studies evaluating healthy pig gut microflora 12 , 24 . Similarly, the increase in the relative proportion of Proteobacteria following some form of intestinal stress has also been reported 27 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The phyla profile in sow‐fed piglets in this study is similar to that reported in previous studies evaluating healthy pig gut microflora 12 , 24 . Similarly, the increase in the relative proportion of Proteobacteria following some form of intestinal stress has also been reported 27 …”
Section: Discussionsupporting
confidence: 89%
“…One of the primary limitations of this study in relation to alterations in intestinal microflora was the short study duration because the microflora continue to adjust and adapt over time, particularly in the very young. A stable microflora may not be established prior to 14 days following an intestinal upset or change in dietary supply, 24 , 32 , 33 and thus longer term studies are required. The JC model more closely reflects the anatomical features in infants with SBS and thus was included in this study; however, it is difficult to maintain JC model piglets in a relative “healthy” state for long‐term studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Matched with previous studies related to microbial diversity in pigs, Firmicutes, Bacteroidetes, and Proteobacteria were the main ubiquitous members in pig intestinal tract and were not easily affected by other factors such as host genotype, disease, and diet [10,13].…”
Section: Shifts Of Dominant Bacterial Communitiesmentioning
confidence: 58%
“…Extracted DNA was quantified by the NanoDrop spectrophotometer (Thermo scientific). The V5-V6 hypervariable region of the 16S rRNA was PCR amplified from microbiome genomic DNA with sample-specific sequence barcoded fusion primers [13] (forward 5 0 AYTGGGYDT AAAGNG3 0 , reverse 5 0 TACNVGGGTATCTAATCC3 0 ). The PCR program used was at 94°C for 5 min; 30 cycles of 94°C for 30 s, 55°C for 30 s, and 72°C for 30 s; followed by 72°C for 7 min and ended with 4°C.…”
Section: S Rrna Amplification and Sequencingmentioning
confidence: 99%